Effect of point mutations on Herbaspirillum seropedicae NifA activity - B. Aquino; A.A. Stefanello; M.A.S. Oliveira; F.O. Pedrosa; E.M. Souza; R.A. Monteiro; L.S. Chubatsu (Brazilian Journal of Medical and Biological Research, 2015)
NifA is the transcriptional activator of the nif genes in Proteobacteria. It is usually regulated by nitrogen and oxygen, allowing biological nitrogen fixation to occur under appropriate conditions. NifA proteins have a typical three-domain structure, including a regulatory N-terminal GAF domain, which is involved in control by fixed nitrogen and not strictly required for activity, a catalytic AAA+ central domain, which catalyzes open complex formation, and a C-terminal domain involved in DNA-binding. In Herbaspirillum seropedicae, a β-proteobacterium capable of colonizing Graminae of agricultural importance, NifA regulation by ammonium involves its N-terminal GAF domain and the signal transduction protein GlnK. When the GAF domain is removed, the protein can still activate nif genes transcription; however, ammonium regulation is lost. In this work, we generated eight constructs resulting in point mutations in H. seropedicae NifA and analyzed their effect on nifH transcription in Escherichia coli and H. seropedicae. Mutations K22V, T160E, M161V, L172R, and A215D resulted in inactive proteins. Mutations Q216I and S220I produced partially active proteins with activity control similar to wild-type NifA. However, mutation G25E, located in the GAF domain, resulted in an active protein that did not require GlnK for activity and was partially sensitive to ammonium. This suggested that G25E may affect the negative interaction between the N-terminal GAF domain and the catalytic central domain under high ammonium concentrations, thus rendering the protein constitutively active, or that G25E could lead to a conformational change comparable with that when GlnK interacts with the GAF domain.